Comparison of the hospital costs for two-stage reimplantation for deep infection, single-stage revision and primary total elbow arthroplasty. Issue 4 (October 2017) - Wagner, Eric R.; Ransom, Jeanine E.; Kremers, Hilal Maradit; Morrey, Mark; Sanchez-Sotelo, Joaquin
Background: The purpose of the present study was to determine the cost of two-stage reimplantation for the treatment of deep infection after total elbow arthroplasty (TEA) and compare this with primary and aseptic revision TEA. Methods: Three hundred and seventy-one primary TEA and 286 revision TEAs (including 47 elbows requiring two-stage reimplantation) were performed. Total direct medical costs during each hospitalization were obtained from our institutional research database and compared for three groups: primary TEA, revision for nonseptic reasons and two-stage reimplantation for deep infection. Results: The mean cost of an uncomplicated primary TEA and aseptic revision TEA was $18, 464 and $18, 796, respectively. The mean overall cost associated with two-stage reimplantation increased to $34, 286. Two-stage reimplantation increased both Part A (hospital costs) and Part B (professional costs). The mean Part A cost for septic revision TEA was $29, 102 versus $15, 844 for primary TEA. The mean Part B cost for septic revision TEA was $5, 184 versus $2, 621 for primary TEA. Conclusions: Two-stage reimplantation for treatment of an infected TEA costs 186% the hospital cost of a primary uncomplicated or aseptic revision TEA. The overall cost to society is even greater if we take into account the cost of antibiotic therapy in between stages and lost days from work.